FABRICATION AND CHARACTERIZATION OF CARBON COMPOSITE FROM COCONUT SHELL CARBON - Meytij Jeanne Rampe; Bambang Setiaji; Wega Trisunaryanti; Triyono Triyono (Indonesian Journal of Chemistry, 2011)
Structure and chemical composition of coconut shell carbon with polyvinyl alcohol (PVA) as the stimulant through the observation of TG-DTA, SEM-EDS and FTIR has been studied. The process was carried out by calcining coconut shell charcoal at the temperature of 873 and 1023 K under Nitrogen flow, then mixed with polyvinyl alcohol (PVA) under composition of 2.5 to 7.5% (wt) in water solvent. The growing of carbon composite structure was observed by heating the samples in Argon gas of 1673 K, the rate of temperature was 10 K/min in 3 h. The products were then analyzed by TG-DTA, SEM-EDS, FTIR and XRD. The result showed that the products were in uniform particle sizes of micrometer dimensions and spherical particles shape, with average content of C element was 97.44% (wt), aromatic character and semi-crystalline structure.